2018
DOI: 10.1002/ange.201712851
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Branched‐Chain Sugars with a DHAP‐Dependent Aldolase: Ketones are Electrophile Substrates of Rhamnulose‐1‐phosphate Aldolases

Abstract: Dihydroxyacetone phosphate(DHAP)-dependent rhamnulose aldolases display an unprecedented versatility for ketones as electrophile substrates. We selected and characterized a rhamnulose aldolase from Bacteroides thetaiotaomicron (RhuABthet) to provide a proof of concept. DHAP was added as a nucleophile to several -hydroxylated ketones used as electrophiles. This aldol addition was stereoselective and produced branchedchain monosaccharide adducts with a tertiary alcohol moiety. Several aldols were thus readily o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…1, dark blue broken line arrows, followed by light green lines for the strictly anaerobic section). There, MTRu-1-P is first cleaved into dihydroxyacetone phosphate (DHAP) and 2-(methylthio) acetaldehyde (North et al, 2017), using a class II aldolase-like protein that belongs to a family of promiscuous DHAP-dependent enzymes widely spread in bacteria (Laurent et al, 2018). A similar pathway may exist in other bacteria as well, but this has not been explored yet.…”
Section: A Pathway For Anaerobic Ethylene Synthesis In Bacteriamentioning
confidence: 99%
“…1, dark blue broken line arrows, followed by light green lines for the strictly anaerobic section). There, MTRu-1-P is first cleaved into dihydroxyacetone phosphate (DHAP) and 2-(methylthio) acetaldehyde (North et al, 2017), using a class II aldolase-like protein that belongs to a family of promiscuous DHAP-dependent enzymes widely spread in bacteria (Laurent et al, 2018). A similar pathway may exist in other bacteria as well, but this has not been explored yet.…”
Section: A Pathway For Anaerobic Ethylene Synthesis In Bacteriamentioning
confidence: 99%
“…Rhamnose-1-phosphate aldolase (RhuAs) is a dihydroxyacetone phosphate-dependent aldolase that can catalyze the cross-aldehyde condensation between dihydroxyacetone phosphate and dihydroxyacetone. Laurent et al (2018) explored the scope of electrophilic substrates for this type of enzyme, and confirmed that it has strong substrate promiscuity ( Supplementary Table 1 , entries 58–67).…”
Section: Aldolasesmentioning
confidence: 79%
“…Aldolase catalysed asymmetric C−C bond formation plays a pivotal role in the synthesis of many chiral building blocks, natural compounds, pharmaceuticals and has been industrially applied on a multi ton scale . Due to this wide‐ranging utility, its relevance for synthetic chemistry is well recognized .…”
Section: Introductionmentioning
confidence: 99%